Elmer Gertz papers - Gertz, Elmer, 1906-2000.; Gertz, Elmer, 1906-2000.; Gertz, Elmer, 1906-2000.
Personal, family, and professional correspondence; memoranda, opinions, orders, briefs, writs, motions, petitions, exhibits, transcripts, and other legal papers; speeches, writings, and research material; and subject files, family papers, printed matter, and mss. collected by Gertz. The bulk of the collection (1926-1988) relates to Gertz's career as a lawyer in cases involving censorship, housing, libel, obscenity, capital punishment, copyright issues, and the death penalty and as the author of Frank Harris: A Study in Black and White (1931), Odyssey of a Barbarian: the Biography of George Sylvester Viereck (1979), and other works. Represented in the papers are clients Nathan Freudenthal Leopold in his suit against Meyer Levin, Henry Miller, and Jack Ruby and the case Gertz v. Robert Welch, Inc.
Also reflected is Gertz's involvement with the Illinois constitutional convention (1969-1970), Chicago Bar Association, Illinois Coalition Against the Death Penalty, Chicago Citizens Commission to Study the Disorders of Convention Week (1968 Democratic national convention), the Blind Service Association, Caxton Club, and Decalogue Society of Lawyers. Gertz's interest in such literary and historical figures as James Baldwin, Clarence Darrow, Frank Harris, John F. Kennedy, Henry Miller, Carl Sandburg, Bernard Shaw, and Harry S. Truman is also documented.
Correspondents include Louis Adamic, George Anastaplo, Allen Crandall, Paul Crump, Richard J. Daley, Richard M. Daley, Lord Alfred Bruce Douglas, Paul Howard Douglas, Albert Einstein, Otto Eisenschiml, Eli E. Fink, Sigmund Freud, Theodore G. Gertz, Wayne B. Giampietro, Arthur J. Goldberg, Frank Harris, Margery A. Hechtman, Samuel G. Herman, John F. Kennedy, Nathan Freudenthal Leopold, Gene Lovitz, Carey McWilliams, Russ Meyer, Henry Miller, Hesketh Pearson, Muriel Peters, Peter Pollack, Leo Calvin Rosten, Jack Ruby, William F. Ryan, Carl Sandburg, Edward P. Schwartz, Upton Sinclair, Kate Stephens, A. I. Tobin, George Sylvester Viereck, Peter Robert Edwin Viereck, and William W. Witherspoon.
Microfilm only of Sigmund Freud's letters to George Sylvester Viereck
Microfilm.
Location of original Freud-Viereck letters is unknown.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Lawyer, author, and manuscript collector. Died 2000.
Keywords: Adamic, Louis, -- 1899-1951 -- Correspondence; Anastaplo, George, -- 1925- -- Correspondence; Baldwin, James, -- 1924-1987.; Crandall, Allen, -- 1896-1973 -- Correspondence; Crump, Paul -- Correspondence; Daley, Richard J., -- 1902-1976 -- Correspondence; Daley, Richard M. -- 1942- -- Correspondence; Darrow, Clarence, -- 1857-1938.; Douglas, Alfred Bruce, -- Lord, -- 1870-1945 -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Eisenschiml, Otto, -- 1880-1963 -- Correspondence; Fink, Eli E., -- 1907-1979 -- Correspondence; Freud, Sigmund, -- 1856-1939 -- Correspondence; Gertz, Theodore G. -- Correspondence; Giampietro, Wayne B. -- 1942- -- Correspondence; Goldberg, Arthur J. -- Correspondence; Harris, Frank, -- 1856-1931.; Harris, Frank, -- 1856-1931 -- Correspondence; Hechtman, Margery A. -- Correspondence; Herman, Samuel G. -- Correspondence; Kennedy, John F. -- 1917-1963.; Kennedy, John F. -- 1917-1963 -- Correspondence; Leopold, Nathan Freudenthal, -- 1904-1971.; Leopold, Nathan Freudenthal, -- 1904-1971 -- Correspondence; Levin, Meyer, -- 1905-1981.; Lovitz, Gene -- Correspondence; McWilliams, Carey, -- 1905-1980 -- Correspondence; Meyer, Russ, -- 1922- -- Correspondence; Miller, Henry, -- 1891-1980 -- Correspondence; Pearson, Hesketh, -- 1887-1964 -- Correspondence; Peters, Muriel -- Correspondence; Pollack, Peter, -- 1909-1978 -- Correspondence; Rosten, Leo, -- 1908-1997 -- Correspondence; Ruby, Jack; Ruby, Jack -- Correspondence; Ryan, William F., -- 1922-1972 -- Correspondence; Sandburg, Carl, -- 1878-1967.; Sandburg, Carl, -- 1878-1967 -- Correspondence; Schwartz, Edward P. -- Correspondence; Shaw, Bernard, -- 1856-1950.; Sinclair, Upton, -- 1878-1968 -- Correspondence; Stephens, Kate, -- 1853-1938 -- Correspondence; Tobin, A. I. -- Correspondence; Truman, Harry S., -- 1884-1972.; Viereck, George Sylvester, -- 1884-1962 -- Correspondence; Viereck, Peter, -- 1916-2006 -- Correspondence; Witherspoon, William W. -- Correspondence; Blind Service Association; Caxton Club; Chicago Bar Association; Chicago Citizens Commission to Study the Disorders of Convention Week; Decalogue Society of Lawyers; Illinois Coalition Against the Death Penalty; Illinois. -- Constitutional Convention -- (1969-1970); Robert Welch, Inc. -- Trials, litigation, etc; American literature -- 20th century; Capital punishment; Censorship; Copyright